2019
DOI: 10.4067/s0718-09342019000300736
|View full text |Cite
|
Sign up to set email alerts
|

La presencia de elementos de conexión en las producciones narrativas escritas en una muestra de escolares de Santiago de Chile

Abstract: Writing constitutes a social and cultural practice, in which students early on integrate their experiences and demands by means of a cognitive process situated in a spatiotemporal context and cultural environment (Barton, Hamilton & Ivanic, 2000; Castelló, 2002), organised in a suite of coherent utterances by means of various linguistic resources, where connective elements (conjunctions, adverbs or grammaticalised expressions) stand out. This practice commences early and requires linguistic and cognitive abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…= 26; r (e.) = 4; p <.005). According to these results, we can assume similarities to the investigations that have revealed benefits in the provocation of written production when students take control to generate macrostructures of the text with creativity and independence (Atasoy & Temiskan, 2016;Díaz, 2018), as applied through the intervention from virtual learning environments (VLE). Some results located in students who carry out written production through personal interactions have also reported that it corresponds to the interaction on digital platforms, allowing the power to participate in their creations as well as that of their peers as active contributors (Angoma, 2016;Katerniak & Loboda, 2016).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…= 26; r (e.) = 4; p <.005). According to these results, we can assume similarities to the investigations that have revealed benefits in the provocation of written production when students take control to generate macrostructures of the text with creativity and independence (Atasoy & Temiskan, 2016;Díaz, 2018), as applied through the intervention from virtual learning environments (VLE). Some results located in students who carry out written production through personal interactions have also reported that it corresponds to the interaction on digital platforms, allowing the power to participate in their creations as well as that of their peers as active contributors (Angoma, 2016;Katerniak & Loboda, 2016).…”
Section: Resultsmentioning
confidence: 56%
“…Because of considering them basic competences for the human being, they are dimensioned in: (a) adaptation of the text, (b) cohesion and coherence in the organization of ideas, (c) use of conventional language systems, (e) reflection and continuous assessment. Some evidence in this regard shows that all dimensions must be developed at the same time, because they must be understood as concatenated elements, avoiding considering them as progressive levels (Atasoy & Temiskan, 2016), as well as, it has been found that if there are problems for control and develop basic skills, then the higher ones would present similar problems from the school stage (Díaz, 2018), especially in subsidized schools. On the contrary, given the need for students to develop these dimensions in parallel, we find evidence that contradicts these proposals, since it has been found that the major problem lies in the transfer of written content to another language, and in the capitalization of the text (generation of macro ideas) (Ratnaningsih, 2019), instead of the competences of cohesion, coherence, adequacy and reflection, although in the Latin American evidence there are coincidences on the parallel education of the dimensions of written expression (Atasoy & Temiskan, 2016;Sánchez & López, 2019).…”
Section: Findings In the Written Expression And In The Approaches Of mentioning
confidence: 99%
“…Los resultados muestran que, en función de los componentes del ECAN, la calidad narrativa está asociada primordialmente con la cohesión, la coherencia local, las figuras retóricas, la coherencia pragmática y, finalmente, la coherencia global. Dichos componentes se constituyen en un aporte para el estudio de la calidad narrativa en la medida en que se superan formas fragmentarias de análisis donde solamente se mide la cohesión y coherencia para establecer conexión al interior de los textos o como únicos indicadores de calidad narrativa (Babaei et al, 2019;Díaz Oyarce, 2019;); también, se traspasa la limitación de los estudios tradicionales centrados en elementos de orden gramatical y ortográfico (Fernández et al, 2019). Por lo tanto, un aporte que se realiza con este estudio se orienta hacia clarificar el peso de cada componente en la calidad narrativa en relatos de guion de base segura.…”
Section: Discussionunclassified
“…En correspondencia a lo manifestado, es posible inferir que la dimensión literaria es una realidad practicada frecuentemente; lo lamentable y contradictorio, es evidenciar que el fin por el que se realizan dichas publicaciones, es decir, la lectura, según el autor aludido anteriormente, es escasa; es esta realidad la que supone un declive en el consumo de dichas producciones (Oyarce, 2019).…”
Section: Producción Literaria En La Actualidadunclassified